2020
DOI: 10.1111/jifm.12120
|View full text |Cite
|
Sign up to set email alerts
|

Analyst following, disclosure quality, and discretionary impairments: Evidence from China

Abstract: Financial statement preparers' discretion in fair value measurements is integral to asset impairment accounting. Firms may misuse this discretion to report more or less impairment loss than is warranted by underlying economic circumstances. Using data from a sample of publicly listed firms in China, this study finds that analyst following reduces abnormal impairment loss, the portion of reported impairment loss that cannot be explained by corporate economic circumstances and that this effect is more pronounced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…To better obtain the net effect of PPBA on corporate accounting information disclosures, we also controlled for the variables that are thought to affect corporate accounting information disclosure behavior (Cascino et al, 2010; Dhole et al, 2020; Hribar et al, 2022). First, as a previous study pointed out that corporate finance characteristics are an important factor affecting the disclosure of corporate accounting information (Jiang, 2020; Ran et al, 2015; Velte, 2021), we controlled for corporate finance characteristics such as Firm size , Leverage rate , Profit growth, Asset turnover , and Stock returns . Second, given that a number of studies have shown that firms with better corporate governance are more likely to disclose high‐quality accounting information (Li et al, 2022; Ran et al, 2015; Zaman et al, 2022), we also controlled for several variables for the quality of corporate governance, including Board size , Independent directors, and Executive shareholding .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To better obtain the net effect of PPBA on corporate accounting information disclosures, we also controlled for the variables that are thought to affect corporate accounting information disclosure behavior (Cascino et al, 2010; Dhole et al, 2020; Hribar et al, 2022). First, as a previous study pointed out that corporate finance characteristics are an important factor affecting the disclosure of corporate accounting information (Jiang, 2020; Ran et al, 2015; Velte, 2021), we controlled for corporate finance characteristics such as Firm size , Leverage rate , Profit growth, Asset turnover , and Stock returns . Second, given that a number of studies have shown that firms with better corporate governance are more likely to disclose high‐quality accounting information (Li et al, 2022; Ran et al, 2015; Zaman et al, 2022), we also controlled for several variables for the quality of corporate governance, including Board size , Independent directors, and Executive shareholding .…”
Section: Methodsmentioning
confidence: 99%
“…finance characteristics are an important factor affecting the disclosure of corporate accounting information (Jiang, 2020;Ran et al, 2015;Velte, 2021), we controlled for corporate finance characteristics such as Firm size, Leverage rate, Profit growth, Asset turnover, and Stock returns. Second, given that a number of studies have shown that firms with better corporate governance are more likely to disclose high-quality accounting information (Li et al, 2022;Ran et al, 2015;Zaman et al, 2022), we also controlled for several variables for the quality of corporate governance, including Board size, Independent directors, and Executive shareholding.…”
Section: Control Variablesmentioning
confidence: 99%
“…Their result found that in a setting where there is high expropriation likelihood, minority shareholders will put more value on private information and, hence, rely more on analyst following. In China, Jiang (2020) found that analyst following results in the high quality of financial statements, especially in terms of fair value recognition, as analyst following reduces abnormal impairment loss and this effect prevails for firms with lower information disclosure quality. Wang and Yu (2021) found that the effect of analysts' forecast accuracy is influenced by whether the country is a code or common law country.…”
Section: Introductionmentioning
confidence: 99%